PENGARUH PENERAPAN KESELAMATAN DAN KESEHATAN KERJA LINGKUNGAN TERHADAP PRODUKTIVITAS TENAGA KERJA KONSTRUKSI: (Studi Kasus : Proyek Paket II Pekerjaan Fisik Jalan Ruas Tana Toraja ). - Marcelina Kabanga; Yessy C. S. Pandeirot; Shirly S. Lumeno, (Sustainable Construction (SUSCON), 2023)
The work of a project has a very large level of risk and danger. Therefore, all construction projects should have an OHS program in order to minimize the accident rate. If the work environment and occupational health and safety (K3) are not supportive, it will have an impact on labor productivity. The purpose of this study was to determine the application of environmental occupational safety and health (K3L) to workers in the Package II Physical Works Project for the Tana Toraja Road, to determine the effect of implementing environmental occupational safety and health (K3L) on labor productivity in the Package II Project. Physical Work on the Tana Toraja Toll Road and determine the workers' compliance with the K3 rules that exist in the Package II Project for Physical Work on the Tana Toraja Road. From the results of observations and literature studies, there are variables to be studied, namely 9 variables of safety implementation (X1), 6 variables of occupational health and health (X2), and 10 variables of labor productivity (Y) which are arranged in a questionnaire. Data collection using a questionnaire was given to 45 respondents as well as interviews. The collected data was then analyzed using the Multiple Linear Regression analysis technique with the SPSS 25 program and proving the results through manual comparison tests. Based on the results of multiple linear regression analysis, the equation obtained from the SPSS test is: Y = 30,914 + 0.050 X1 + 0.499 X2 and the equation obtained by manual testing is: Y = 36,287 + 0,080X1 + 0,51 X2; whrere Y=work productivity,X1= work safety,X2=work environment health